Low Noise Figure of Cascaded LNA at 5.8GHz Using T-Matching Network for WiMAX Applications - Othman , A.R; Ibrahim, A.B; Husain, M.N; Hamidon A.H, A.H; Hamidon , Jsam (2012)
This project presents the low Noise Figure (NF) cascaded Low Noise Amplifier (LNA) at 5.8GHz using T-matching network applicable for WiMAX application. The amplifier used FHX76LP Low Noise SuperHEMT FET. The LNA designed used T-matching network consisting of lump reactive element at the input and the output terminal. The cascaded LNA produced noise figure of 1.3 dB and forward gain of 36.8 dB. The input reflection (S11) and output return loss (S22) are -12.4 dB and -12.3 dB respectively. The bandwidth of the amplifier is more than 1.24 GHz. The input sensitivity is compliant with the IEEE 802.16 standards.